Crisis Psychosomatic Dysregulation as a Clinical Phenomenon: Neurobiological Mechanisms, Clinical Phenotypes, and Stabilization Strategies - Khaustova, Olena; Sak, Lesia (Psychosomatic Medicine and General Practice, 2026)
Background. In contemporary clinical practice, painful conditions characterized by an abrupt exacerbation of somatic symptoms accompanied by affective and cognitive disorganization are increasingly observed across different diagnostic categories. To conceptually describe these conditions, the working term "psychosomatic storms" is used, reflecting a crisis form of psychophysiological dysregulation. Although this phenomenon does not represent an independent diagnostic entity, it has substantial clinical relevance because it is associated with severe distress, limited response to standard treatment, and significant impairment in patients’ quality of life. Objective. To summarize current evidence regarding psychosomatic storms as a clinical phenomenon, analyze their neurobiological mechanisms, describe their principal clinical phenotypes, and substantiate differentiated stabilization strategies according to the level of psychophysiological dysregulation. Methods and Materials .A narrative review of the contemporary literature published between 2020 and 2026 was conducted using PubMed, Scopus, the Cochrane Library, and Embase. The review focused on studies addressing interoception, large-scale brain networks (the salience network, default mode network, and executive control network), anxiety disorders, somatic symptom disorders, post-traumatic stress disorder, and pharmacological and psychotherapeutic interventions. Interpretation of the findings was complemented by the authors’ extensive clinical experience. Results. Psychosomatic storms may be conceptualized as a consequence of an imbalance between hyperactivation of the salience network and insufficient regulatory control exerted by executive brain systems. The central mechanism involves disturbed interoceptive processing within the predictive coding framework, leading to the misinterpretation of bodily sensations as threatening and the development of a self-perpetuating cycle of somatic symptoms, anxiety, autonomic activation, and symptom amplification. Four major clinical phenotypes were identified: autonomic crisis, somatoform, dissociative, and psychoaffective. Each phenotype is characterized by a distinct combination of neurobiological and psychopathological mechanisms. Standard therapeutic approaches, including selective serotonin reuptake inhibitors and psychotherapy, may be insufficient in a subset of patients because the level of intervention does not adequately correspond to the severity of systemic dysregulation. In such cases, treatment intensification with second-generation antipsychotics possessing a broad receptor profile, particularly olanzapine, may be justified. Conclusions. Psychosomatic storms represent a clinically meaningful phenomenon reflecting the breakdown of integrative regulatory mechanisms linking bodily, affective, and cognitive processes. Their management requires a mechanism-oriented clinical approach based on timely recognition of the crisis state, identification of the predominant dysregulation mechanism, implementation of stepwise stabilization strategies, and subsequent integration of psychotherapeutic interventions. Keywords: psychosomatic disorders; psychosomatic medicine; chronic stress; interoception; somatization; dissociation; anxiety disorders; post-traumatic stress disorder; psychotherapy; psychopharmacotherapy; psychophysiological dysregulation.